Analytical Modeling and Performance Characterization of a Double Gate MOSFET with Dielectric Pockets Incorporating Work Function Engineered Binary Metal Alloy Gate Electrode for Subdued SCEs. Issue 5 (3rd September 2018) - Saha, Ranita; Sarkhel, Saheli; Sarkar, Subir Kumar
ABSTRACT: In this work, double gate MOSFET with dielectric pocket has been proposed by incorporating the concept of gate work function engineering. A comparative analysis of this proposed structure with a normal double gate dielectric pocket MOSFET without gate work function engineering has been investigated in terms of surface potential, channel electric field distribution, and threshold voltage in order to establish the superiority of the proposed structure in subduing short channel effects. The analytical results are in good agreement with simulated results, thereby validating the accuracy of the analytical model.